METHODOLOGY OF LABORATORY LESSONS IN ELECTRICAL ENGINEERING - Khudoyberganov S.B.; Kurbanov I.B.; Nuriddinov S.B.; Avazov B.K. (Journal of new century innovations, 2022)
A laboratory workshop's goal is usually to: specify abstract educational material and deepen the concepts studied in theoretical courses, teach practical research methods and the ability to use special experimental tools; instill general and specific experimentation skills; and form practical skills in setting up devices and conducting electrical circuit measurements. In most cases, the stated duties can be solved to some degree using the usual method of arranging and conducting laboratory classes. However, this is insufficient, because a modern specialist must be trained to acquire knowledge freely, think creatively, and communicate effectively in the workplace.